Differences in larval morphology of allopatric isolated populations of the odontophrynus occidentalis group from western argentina - Cei, José Miguel Alfredo María (1982)
A morphological comparative study of two larval populations - one from Mendoza and the other an isolated one from Sierra Famatina (La Rioja) - of the Argentine toad, Odontophrynus occidentalis, is reported.